YOGA PRANAYAMA LOWERS THE RISK OF VIOLENT BEHAVIOR IN SCHIZOPHRENIA PATIENTS - Desak Made Ari Dwi Jayanti; I Made Dwi Satwika Wiraputra; Ni Ketut Ayu Mirayanti (Sport and Fitness Journal, 2021)
Introduction:The main problem that often occurs in schizophrenic patients is violent behavior. As a result of violent behavior can hurt or injure yourself or others. Handling violent behavior is done by a combination of psychopharmacology and psychotherapy intervention. One of the management of violent behavior through individual psychotherapy is physical activity in the form of pranayama yoga exercises. The purpose of this study is to determine the effect of Pranayama yoga on the risk of violent behavior in schizophrenic clients.Method :This type of pre-experimental research, using a One-group pre-post test design. The number of samples is 20 people with simple random sampling. Result : Data collection uses observation sheets. The mean symptom of the risk of violent behavior pre-test of 13.55 including the risk of moderate violent behavior. The average post-test of 5.50 included the risk of mild violent behavior. Paired t test statistic results obtained p value <0.05 means that there are significant differences in symptoms of risk of violent behavior in schizophrenic patients pre-test and post-test it shows there is an influence of pranayama yoga on symptoms of risk of violent behavior in schizophrenic patients. Physical exercise through pranayama yoga exercises in general can reduce physiological stimulation and tension so as to reduce patient anger.Discussion : Based on these results it is recommended that setting a routine schedule for schizophrenics in the Mental Hospital.Introduction:The main problem that often occurs in schizophrenic patients is violent behavior. As a result of violent behavior can hurt or injure yourself or others. Handling violent behavior is done by a combination of psychopharmacology and psychotherapy intervention. One of the management of violent behavior through individual psychotherapy is physical activity in the form of pranayama yoga exercises. The purpose of this study is to determine the effect of Pranayama yoga on the risk of violent behavior in schizophrenic clients.Method :This type of pre-experimental research, using a One-group pre-post test design. The number of samples is 20 people with simple random sampling. Result : Data collection uses observation sheets. The mean symptom of the risk of violent behavior pre-test of 13.55 including the risk of moderate violent behavior. The average post-test of 5.50 included the risk of mild violent behavior. Paired t test statistic results obtained p value <0.05 means that there are significant differences in symptoms of risk of violent behavior in schizophrenic patients pre-test and post-test it shows there is an influence of pranayama yoga on symptoms of risk of violent behavior in schizophrenic patients. Physical exercise through pranayama yoga exercises in general can reduce physiological stimulation and tension so as to reduce patient anger.Discussion : Based on these results it is recommended that setting a routine schedule for schizophrenics in the Mental Hospital.